Protecting Lemon From Juices (Texas Journal of Agriculture and Biological Sciences, 2023)
In the article, 2 classes of 25 types of pests belonging to different families have been identified on citrus plants in the conditions of the Republic. Among them, among the dominant species that cause the main damage: mites (Acariphormes) belonging to the family of spider mites (Tetranychidae) and representatives of the class of insects are found to be greenhouse and cotton aphids, acacia, peach and polysis aphids